A Replicable Model for Climate Resilience Across Agro-Climatic Zones: Evidence from Maharashtra - Agarwal, Prabhat (Journal of Social Science and Humanities, 2026)
Watershed Development projects have been implemented all over to address the soil and water conservation issues and social capital formation since long. However, climate change is impacting the agricultural production, productivity, livelihood and income of the farmers severely due to uncertain and erratic changes in weather parameters especially temperature, humidity and rainfall. Thus, there was need to superimpose climate change mitigation and adaption measures on the completed watersheds so we can climate proof the watersheds. Thus, Climate proofing Programme was initiated by NABARD in 2017 and it was implemented by BAIF Development Research Foundation implemented in 19 villages across various Agro climatic zones in Maharashtra. Over a period of 4 years, a range of interventions were undertaken in different agro climatic zones susceptible to diverse climatic risks. This case study highlights the effective climate interventions that were used to reduce vulnerabilities, along with the methodologies behind them in order to build resilience among different communities in Maharashtra. Further, it explores the need and potential for Replication of such climate interventions to increase the adaptive capacities of communities in different agro climatic zones in line with the climate - specific needs of the region. The case study examines three key aspects in which the project can be replicated. The first is the institutional methodology of Region- specific approach for implementation of climate - proofing interventions. Second, demonstrating effective low - carbon, climate - resilient technologies and systems can facilitate scale - up and replication. Third, it discusses the effectiveness of the bottom - Up Approach for Implementation of climate adaptation and mitigation measures: Fourth, the cluster level approach for Addressing Knowledge Gaps can be recommended in all the climate change projects and programmes in India.